Promotion of lung tumor growth by interleukin-17 - Xu, Beibei (American Physiological Society, 2014)
Recent findings demonstrate that inhaled cigarette smoke, the predominant lung carcinogen, elicits a T helper 17 (Th17) inflammatory phenotype. Interleukin-17A (IL-17), the hallmark cytokine of Th17 inflammation, displays pro- and antitumorigenic properties in a manner that varies according to tumor type and assay system. To investigate the role of IL-17 in lung tumor growth, we used an autochthonous tumor model (K-Ras(LA1) mice) with lung delivery of a recombinant adenovirus that expresses IL-17A. Virus-mediated expression of IL-17A in K-Ras(LA1) mice at 8–10 wk of age doubled lung tumor growth in 3 wk relative to littermates that received a green fluorescent protein-expressing control adenovirus. IL-17 induced matrix metalloproteinase-9 (MMP-9) expression in vivo and in vitro. In accord with this finding, selective and specific inhibitors of MMP-9 repressed the increased motility and invasiveness of IL-17-treated lung tumor cells in culture. Knockdown or mutation of p53 promoted the motility of murine lung tumor cells and abrogated the promigratory role of IL-17. Coexpression of siRNA-resistant wild-type, but not mutant, human p53 rescued both IL-17-mediated migration and MMP-9 mRNA induction in p53 knockdown lung tumor cells. IL-17 increased MMP-9 mRNA stability by reducing interaction with the mRNA destabilizing serine/arginine-rich splicing factor 1 (SRSF1). Taken together, our results indicate that IL-17 stimulates lung tumor growth and regulates MMP-9 mRNA levels in a p53- and SRSF1-dependent manner.